2006
DOI: 10.1097/01.sla.0000242708.51631.66
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Methodologic Quality of Human Therapy Studies in ISI Surgical Publications?

Abstract: The methodologic quality of therapy articles published in the journals analyzed is low; however, statistical significance was determined between them. Association was observed between methodologic quality and origin, but not with subject matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
28

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 11 publications
0
47
0
28
Order By: Relevance
“…Unfortunately, in dentistry 4,5,8 and other biomedical sciences, 6 many published research articles would be considered to have a low LoE. However, LoEs provide an incomplete picture since studies that have the same LoE nominally, may differ in essential methodological aspects (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unfortunately, in dentistry 4,5,8 and other biomedical sciences, 6 many published research articles would be considered to have a low LoE. However, LoEs provide an incomplete picture since studies that have the same LoE nominally, may differ in essential methodological aspects (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,8 An additional advantage of the MINCIR scale is that it enables one to perform systematic reviews of clinical trials, cohort studies, case-control, and case series studies. 11 The MINCIR scale has been used to assess surgical studies, 6 including studies in the areas of oral and maxillofacial surgery, 8 and has demonstrated psychometric properties. 12 However, these may vary depending on the study population; so it is necessary to have validation procedures to assure adequacy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations